Current concepts on epilepsy management in tuberous sclerosis complex. Issue 3 (26th September 2018) - Canevini, Maria Paola; Kotulska‐Jozwiak, Katarzyna; Curatolo, Paolo; La Briola, Francesca; Peron, Angela; Słowińska, Monika; Strzelecka, Jolanta; Vignoli, Aglaia; Jóźwiak, Sergiusz
Abstract : Tuberous sclerosis complex (TSC) is an autosomal dominant neurocutaneous disease affecting approximately 1 in 6, 000 people, and represents one of the most common genetic causes of epilepsy. Epilepsy affects 90% of the patients and appears in the first 2 years of life in the majority of them. Early onset of epilepsy in the first 12 months of life is associated with high risk of cognitive decline and neuropsychiatric problems including autism. Prenatal or early infantile diagnosis of TSC, before the onset of epilepsy, provides a unique opportunity to monitor EEG before the onset of clinical seizures, thus enabling early intervention in the process of epileptogenesis. In this review, we discuss the current status of knowledge on epileptogenesis in TSC, and present recommendations of American and European experts in the field of epilepsy.